Engineering of Peglayted Camptothecin Into Nanomicelles and Supramolecular Hydrogels for Pesticide Combination Control - Zhang, Zhi-Jun; Shang, Xiao-Fei; Yang, Liu; Shi, Yan-Bin; Liu, Ying-Qian; Li, Jun-Cai; Yang, Guan-Zhou; Yang, Cheng-Jie (Frontiers in Chemistry, 2020)
As a famous quinoline alkaloid, camptothecin (CPT) presented the significant anti-tumor activity, as well as the interesting insecticidal activities, but the low solubility, poor hydrophobicity and cuticular penetration of CPT have been severely limited the field application. In this study, we conjugated the camptothecin with polyethylene glycol, forming amphiphilic copolymer, mPEG-CPT, which could be self-assembled into micelles, or formed a hydrogel with α-CD by super-cross-linking to combine delivery with acetamiprid or nitenpyram. Results showed that the nitenpyram or acetamiprid loaded hydrogels showed dual phase release behavior, while the micelles displayed a synchronous and fast release profile, and these four nanopesticides showed potent or superior insecticidal activities and a synergetic effect against Brevicoryne brassicae, Tetranychus cinnabarinus and Bursaphelenchus xylophilus. This finding indicated that micelles and hydrogels could be used as effective carriers for pesticide combination control.